(untitled) (Revista de Ciências Agroveterinárias, 2015)
The urban afforestation is important for the life quality of the populations, however, good planning is required, in order to avoid problems that cause interference with urban elements and biological invasion. This study aimed to perform a quantitative and qualitative survey of the urban trees in squares and main routes of Tenente Portela, RS. Five squares and the six busiest routes in the municipality were inventoried through a census, by analyzing every individual shrub and tree. A total of 743 individual plants belonging to 67 species and 27 botanical families were found, with Ligustrum lucidum being the most abundant species (20.46%). The most abundant family was Bignoniaceae (27%). The mean height and circumference at breast height of the species were, respectively, 5.95 m and 67 cm. Regarding interference, 30% of individuals had canopies interfering with pedestrian or vehicles passages, and 33.8% of trees were damaging the sidewalks due to root outcrops. The general condition of the 455 plants was considered good and 50% of the total was growing under concrete pavement. Although major problems related to the quality of individual plants were not detected, a better planning of afforestation in urban area is necessary and it is expected that the results observed in this study can assist the municipal government in this planning.